(untitled) (European Journal of Marketing and Economics, 2026)
The ecological transformation of the economy poses a number of challenges to the businesses and the government, whilst environmental responsibility in recent decades has been increasingly taken up by a growing number of companies, regardless of their size, business activities, or sector of operation. The objective of research is to analyse what incentive policies the government should set up to promote the ecological transformation of Bulgaria’s economy and what environmental business practices and environmental management systems the firms operating in the Bulgarian market have in place. The analysis is based on an empirical study conducted with 200 business organisations. The results show that the low level and limited scope of the environmental responsibility applied in Bulgaria are associated with the absence of a clearly defined macroeconomic framework for encouraging investments in innovative sustainability and energy efficiency technologies. The conclusions indicate that in order to intensify ecological transformation, a targeted, systematic and rapid macropolicy reform is required (promoting development and deployment of innovative resource and eco-friendly technologies; changing the logics of eco-fiscal policy; ensuring more efficient funding of the ecological transition; activating the financial markets by introducing new instruments of public-private partnership, etc.).The added value of this paper is not only in the analytical examination of the new challenges, but also and above all, in outlining the direction and deriving recommendations for implementing future actions. The methodology employed is based on primary and secondary investigations, statistical and analytical methods of interpreting data, and identifying the major dependencies and issues.